2021
DOI: 10.3390/ijms22073644
|View full text |Cite
|
Sign up to set email alerts
|

Collagen I Modifies Connexin-43 Hemichannel Activity via Integrin α2β1 Binding in TGFβ1-Evoked Renal Tubular Epithelial Cells

Abstract: Chronic Kidney Disease (CKD) is associated with sustained inflammation and progressive fibrosis, changes that have been linked to altered connexin hemichannel-mediated release of adenosine triphosphate (ATP). Kidney fibrosis develops in response to increased deposition of extracellular matrix (ECM), and up-regulation of collagen I is an early marker of renal disease. With ECM remodeling known to promote a loss of epithelial stability, in the current study we used a clonal human kidney (HK2) model of proximal t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 90 publications
1
9
0
Order By: Relevance
“…Previous studies link increased Cx43 expression to inflammation and fibrosis in a model of renal disease, 6,20 while findings from our laboratory report that aberrant Cx43 hemichannel‐mediated ATP release from TGFβ1‐treated tubular epithelial cells evoked phenotypic and functional changes, characteristic of tubular damage 12,21,22 . Consequently, the current study determined if this effect was accentuated in high glucose and if the response could be decreased using Tonabersat, an efficient Cx43 hemichannel blocker.…”
Section: Resultsmentioning
confidence: 80%
“…Previous studies link increased Cx43 expression to inflammation and fibrosis in a model of renal disease, 6,20 while findings from our laboratory report that aberrant Cx43 hemichannel‐mediated ATP release from TGFβ1‐treated tubular epithelial cells evoked phenotypic and functional changes, characteristic of tubular damage 12,21,22 . Consequently, the current study determined if this effect was accentuated in high glucose and if the response could be decreased using Tonabersat, an efficient Cx43 hemichannel blocker.…”
Section: Resultsmentioning
confidence: 80%
“…Perhaps disturbances in the activation of the TGF-β/p38 and TGF-β/Smad2/3 signaling pathways and possible interactions between them in conjunction with the physiological GJIC-independent function of Cx43 lead to the strong attenuation of the profibrotic potential of HBFs AS exposed to TGF-β 1 . The other possible mechanism of FMT attenuation in HBFs AS can be similar to this described in epithelial or osteocyte-like cells where Cx43 interacts directly with integrin α5 [ 68 , 69 ] and indirectly with ECM components, e.g., fibronectin or collagen I [ 70 , 71 , 72 ]. On the other hand, Cx43 can play a role in signal mechanotransduction, which was documented in cardiac fibrosis [ 73 ].…”
Section: Discussionmentioning
confidence: 95%
“…Although a glomerular disease in origin, advanced stages of nephropathy are characterised by severe tubule interstitial inflammation and fibrosis [ 150 ]. Work within our laboratories links altered Cx43 expression to tubule injury in both in vitro [ 108 , 135 , 151 , 152 ] and in vivo [ 108 ] models of disease [ 153 ]. Initial observations identified an approximate 5-fold increase in Cx43 expression in biopsy material from individuals with diabetic nephropathy compared to healthy control [ 151 ], whilst paired-patch electrophysiology and ATP biosensing suggested that this increased expression was paralleled by diminished gap-junction intercellular coupling (GJIC) and increased hemichannel mediated ATP release [ 151 ].…”
Section: Cx43 Hemichannels and Treatment Of Inflammation In Diabetic Kidney Diseasementioning
confidence: 99%
“…Instrumental to cell adhesion and maintenance of polarity, disassembly of cell junction complexes is linked to partial EMT, events which predispose inflammation and fibrosis [ 167 ], the latter of which is contributed to by extracellular matrix (ECM) deposition [ 152 ]. With collagen I increased in the interstitium of UUO mice, an effect lessened in the Cx43 +/− model [ 168 ], we hypothesized that a modified microenvironment may elicit phenotypic changes via increased Cx43 mediated hemichannel ATP release.…”
Section: Cx43 Hemichannels and Treatment Of Inflammation In Diabetic Kidney Diseasementioning
confidence: 99%